THE EFFECTIVENESS OF A TRAINING PROGRAM USING SPECIAL AIDS AND ITS IMPACT ON THE ACCURACY OF LONG-RANGE SHOOTING BASKETBALL FOR PLAYERS OF THE DIWANIYAH EDUCATION TEAM - Karrar Jaafar Abbas (Scholars Digest Publishing, 2024)
Longshot is considered one of the most important shots in basketball, this type of shot is dependent on teams and players for most of a game. The researcher proceeded to determine if it was possible to rectify the shortfall and deficiency associated with long-scoring performance after special exercises were employed using supplementary methods or assistance to performance. This was intended to demonstrate whether or not members of the study sample benefitted from the exercises and methods proposed by the researcher. The investigation is significant because special exercises are created using supplementary methods for altering performance-after mistakes that players make while executing the long-shot basketball skill (not in the basic form), the loss of points during the game, as well as attempts at rehabilitation and growth.
Keywords: skillful shot for the Al-Qadisiya Education Team's players.